Ethical Considerations for Using School-Based Motivational Interviewing with Parents, Teachers, and Students. Issue 1 (2nd January 2020) - Strait, Gerald G.; Strait, Julia Englund; Schanding, Thomas; Anderson, Jacqueline R.; Stinson, Diana; Schmidt, Stephanie; Kim, Samuel Y.
Abstract: Recently, an increasing number of researchers and school psychologists have advocated for the use of School-Based Motivational Interviewing (SBMI) for working directly with students and for consulting with teachers and parents. However, little attention has been given to the possible ethical implications of school psychologists' use of SBMI with various stakeholders in school settings. In this paper, unique ethical challenges are highlighted and recommendations for implementing SBMI techniques in relation to both MI ethical guidelines and the National Association of School Psychologists (NASP) Principles for Professional Ethics are provided.